Development of Flip Book-Based Cooperative Training Module to Enhance The Creative Character of Cooperative Administrators - Jayadi, Ahmad; Ratumbuysang, Monry Fraick Nicky Gillian; Satrio, Adrie; Mansur, Hamsi (Vidya Karya, 2024)
Cooperatives play a key role in supporting the growth and progress of micro, small, and medium enterprises (MSMEs) in various economic sectors. Training can be done to develop the quality of human resources, including training and developing the creative way of thinking of cooperative administrators. This research aims to produce a flip book-based cooperative training module to improve the creative character of cooperative administrators. The research method used is research and development. The modified model used is the ADDIE design. Evaluation by experts and individual trials of the training module resulted in recommendations for revision, receiving a rating of "very good." Research data came from 23 representatives of cooperative administrators who participated in the training, with small group test results also reaching the "very good" category. Data collection was carried out through interviews, group discussions (FGD), consultation with experts, and the distribution of questionnaires. The results of the field trial showed that the flip book-based training module significantly improved the creative thinking abilities of the training participants. Thus, the research results conclude that the flip book-based cooperative training module has been tested for its feasibility and can be effectively used in basic training for cooperative administrators to improve creative character. The increase in creative character can be seen from comparing the pre-test and post-test scores of the training participants. The average pre-test score for training participants before using the flip book-based training module media was 7.36, while the average post-test score for training participants after using the flip book-based training module was 8.23. The students' pre-test and post-test gain test results obtained a score of 69.35% in the "quite effective" category. The increase in creative character can also be seen from the results of the creative character questionnaire for cooperative administrators, which had a percentage value of 81.25% or was categorized as very strong. This means there is a very strong increase in the creative character of cooperative management after attending the training.